Development of the MobQoL patient reported outcome measure for mobility-related quality of life. Issue 23 (6th November 2021) - Bray, Nathan; Spencer, Llinos Haf; Tuersley, Lorna; Edwards, Rhiannon Tudor
Abstract: Purpose: To examine how mobility and mobility impairment affect quality of life; to develop a descriptive system (i.e., questions and answers) for a novel mobility-related quality of life outcome measure. Materials and methods: Data were collected through semi-structured interviews. Participants were recruited predominantly from NHS posture and mobility services. Qualitative framework analysis was used to analyse data. In the first stage of analysis the key dimensions of mobility-related quality of life were defined, and in the second stage a novel descriptive system was developed from the identified dimensions. Results: Forty-six interviews were conducted with 37 participants (aged 20–94 years). Participants had a wide range of conditions and disabilities which impaired their mobility, including cerebral palsy, multiple sclerosis, and arthritis. Eleven dimensions of mobility-related quality of life were identified: accessibility, safety, relationships, social inclusion, participation, personal care, pain and discomfort, independence, energy, self-esteem, and mental-wellbeing. A new outcome measure, known as MobQoL, was developed. Conclusions: Mobility and mobility impairment can have significant impacts on quality of life. MobQoL is the first outcome measure designed specifically to measure the impact of mobility on quality of life, and therefore has utility in research and practice to measure patient outcomes related to rehabilitation. Implications for Rehabilitation: Mobility impairment affects many different aspects of health and quality of life. The impact of mobility impairment on quality of life is related to processes of physical, emotional, and behavioural adaptation. MobQoL is the first patient-reported outcome measure designed specifically to measure the quality of life impacts of mobility impairment and assistive mobility technology use. MobQoL has potential to be used by rehabilitation professionals to measure and monitor mobility-related quality of life as part of routine clinical practice.